2022
DOI: 10.3892/etm.2022.11721
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of progressive ischemic stroke with low‑dose eptifibatide: A retrospective case‑control study

Abstract: Progressive ischemic stroke (PIS) is a therapeutic challenge in clinical practice. The present retrospective study aimed to investigate the safety and effectiveness of eptifibatide in the treatment of PIS. The present study enrolled patients with PIS admitted to Xiangtan Central Hospital (Xiangtan, China) between March 2020 and March 2021 with National Institutes of Health Stroke Scale (NIHSS) progression scores of ≥2 points during the initial 72 h. Patients were then divided into two groups according to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Perhaps, these better clinical outcomes in the eptifibatide group resulted from lower rates of thrombotic and hemorrhagic complications in comparison with patients not receiving this drug (even if these differences in our material were not statistically significant). Theoretically, these differences could be associated with fewer thrombotic occlusions in the cerebral microvasculature [16,[22][23][24]. Of note, reocclusion of the ICA or suboptimal thrombectomy are independent predictors of the intracranial bleeding in the settings of ischemic stroke [16,26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps, these better clinical outcomes in the eptifibatide group resulted from lower rates of thrombotic and hemorrhagic complications in comparison with patients not receiving this drug (even if these differences in our material were not statistically significant). Theoretically, these differences could be associated with fewer thrombotic occlusions in the cerebral microvasculature [16,[22][23][24]. Of note, reocclusion of the ICA or suboptimal thrombectomy are independent predictors of the intracranial bleeding in the settings of ischemic stroke [16,26].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, reocclusion of the ICA or suboptimal thrombectomy are independent predictors of the intracranial bleeding in the settings of ischemic stroke [16,26]. In the study by Renu et al, it was found that the highest rate of bleeding complications occurred in the group in which stent implantation was used in combination with antiplatelet drug, but there was either a suboptimal intracranial recanalization (TICI ≤ 2a) or there was stent thrombosis [23]. Probably, incomplete recanalization and damage to the blood-brain barrier, in combination with the antiplatelet drugs, increased the risk of intracranial bleeding [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FDA indicates its use for the treatment of ACS and in percutaneous coronary intervention (PCI) [ 68 ]. However, research over the past decade has also sought to evaluate the role of eptifibatide in ischemic stroke, stenting of carotid and intracranial aneurysms, and septic shock [ 68 , 69 , 70 , 71 , 72 , 73 ]. In Table 2 we present summary of recently published meta-analyses.…”
Section: Eptifibatidementioning
confidence: 99%
“…A newer retrospective case-control study by Luo et al (2022) compared routine therapy and treatment with an additional low dose of eptifibatide. Although the study reported no significant differences in NIHSS or adverse events, an analysis of the subgroups showed that eptifibatide is a safe and effective treatment when small artery occlusion is involved [ 71 ]. Similarly, a trial by Rana et al from 2022 showed that using eptifibatide during endovascular therapy in large vessel occlusion is associated with a higher rate of hemorrhages and no benefits to the NIHSS or 90-day mortality [ 101 ].…”
Section: Eptifibatidementioning
confidence: 99%